Greenhouse gas mitigation and hydrogen generation via enhanced ethylene glycol dry reforming on La-promoted Co/Al2O3 catalyst - Lau, N. Jun; Mahadi, Bahari; Setiabudi, H. D.; A. A., Jalil; Vo, Dai-Viet N. (Elsevier, 2021)
The first investigation of La-promoted Co/Al2O3 catalysts in Ethylene Glycol-CO2 conversion (EGCC) for syngas (H2 + CO) production was conducted in this work. Co/Al2O3 catalysts modified with different La promoter loadings (1, 3, and 5%) were generated through sequential incipient wetness impregnation technique and employed for EGCC. The physicochemical attributes of the generated catalysts were examined via Brunauer-Emmett-Teller (BET), H2 temperature-programmed reduction (H2-TPR), X-ray diffraction (XRD), Raman, and temperature-programmed oxidation (TPO). 3%La-promoted catalyst owned the largest specific surface area, smallest Co crystallite size of 9.8 nm, and lowest reduction temperature among the promoted catalysts. These excellent properties resulted in the highest catalytic performance on the 3%La-promoted catalyst (i.e., C2H6O2 conversion = 77.6 %, CO2 conversion = 43.1 %, H2 yield = 75.3 %, and CO yield = 76.8 %). The significant reduction in carbon deposition of the 3%La-promoted catalyst was due to the La capability in eliminating deposited carbon via the formation of intermediate lanthanum dioxycarbonate, La2O2CO3.